2021
DOI: 10.3390/atmos12050602
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the Ionosphere in Middle Latitudes during 2009, 2018 and 2018/2019 Sudden Stratospheric Warming Events

Abstract: The ionospheric weather is affected not only from above by the Sun but also from below by processes in the lower-lying atmospheric layers. One of the most pronounced atmospheric phenomena is the sudden stratospheric warming (SSW). Three major SSW events from the periods of very low solar activity during January 2009, February 2018, and December 2018/January 2019 were studied to evaluate this effect of the neutral atmosphere on the thermosphere and the ionosphere. The main question is to what extent the ionosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 67 publications
4
13
1
Order By: Relevance
“…We investigated the responses of the equatorial/low‐latitude ionosphere over the African and American sectors to: (a) minor and major winter arctic SSW events (January–April, 2014) and (b) geomagnetic storms that occurred during the same period of the SSW events. The conclusions from this study are: In addition to the roles played by geomagnetic storms and other solar events in space weather, lower atmospheric couplings also play significant roles, particularly in the ionospheric part of space weather (ionospheric weather) (Mosna et al., 2021). With reference to the pre‐SSW quiet days, TEC intensity responded positively to the SSW peak days in both longitudinal sectors, except on February 8 in the African sector, when a negative TEC response was recorded.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We investigated the responses of the equatorial/low‐latitude ionosphere over the African and American sectors to: (a) minor and major winter arctic SSW events (January–April, 2014) and (b) geomagnetic storms that occurred during the same period of the SSW events. The conclusions from this study are: In addition to the roles played by geomagnetic storms and other solar events in space weather, lower atmospheric couplings also play significant roles, particularly in the ionospheric part of space weather (ionospheric weather) (Mosna et al., 2021). With reference to the pre‐SSW quiet days, TEC intensity responded positively to the SSW peak days in both longitudinal sectors, except on February 8 in the African sector, when a negative TEC response was recorded.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to the roles played by geomagnetic storms and other solar events in space weather, lower atmospheric couplings also play significant roles, particularly in the ionospheric part of space weather (ionospheric weather) (Mosna et al., 2021). With reference to the pre‐SSW quiet days, TEC intensity responded positively to the SSW peak days in both longitudinal sectors, except on February 8 in the African sector, when a negative TEC response was recorded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mošna et al. (2021) recently showed nighttime enhancements in the total electron content rate index over Europe during the SSWs of February 2018 and December‐January 2018‐2019 which they ascribe to both lower atmospheric and geomagnetic forcing.…”
Section: Introductionmentioning
confidence: 99%
“…Fagundes et al (2015) also reported large foF 2 variations occurring in the evening/ nighttime over South America during the major SSW of January 2009. Mošna et al (2021) recently showed nighttime enhancements in the total electron content rate index over Europe during the SSWs of February 2018 and December-January 2018-2019 which they ascribe to both lower atmospheric and geomagnetic forcing.…”
mentioning
confidence: 99%